Synthesis of Nano Calcium Carbonate from Egg Shell Wasteto Improve Paving Block Quality: A Literature Review and Bibliometric Analysis - Gabriel Ryan Alfred Balbo (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2023)
This research was conducted to determine (i) the growth in the number of scientific publications in the field of paving block materials with the addition of nano calcium carbonate, (ii) the top citations based on the number citations, and publisher, (iii) visualization of the most productive authors, and (iv) development map publications based on keywords. This research method is quantitative descriptive with bibliometric analysis using Publish or Perish software to obtain data and VOSviewer to visualize related research terms. Data collection was carried out by searching the Google Acholar database with the keywords “calcium carbonate” and “paving blocks” in the period 2011 to 2023. The research results show growth and paving blocks. The most researched subjects in nano calcium carbonate are “calcium carbonate”, “egg shells”, and “pavements”, which are based on overlay and density visualization. The relationships between topics are grouped into fifteen clusters with determine the topics to be researched and can also be a reference for further research.